2008
DOI: 10.4269/ajtmh.2008.79.620
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics of the Antimalarial Drug Piperaquine in Healthy Vietnamese Subjects

Abstract: We compared plasma maximum concentration (Cmax) and area under the concentration-time curve (AUC) of the antimalarial drug piperaquine in 26 healthy Vietnamese subjects after treatment with either a single oral dose of 500 mg (n = 6) or 1,000 mg (n = 6) of piperaquine phosphate and a three-day course of 500 mg of piperaquine/ day in the fasting state (n = 7) or with food (approximately 17 g fat) (n = 7). The geometric mean plasma Cmax and AUC((0-28)) was 2.8-fold (200 ng/mL versus 70 ng/mL) and 1.9-fold (5,736… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(9 citation statements)
references
References 17 publications
0
9
0
Order By: Relevance
“…Previous studies in healthy volunteers reported a large impact on the relative bioavailability of piperaquine after a high-fat meal (13, 14). These differences are likely to be explained by the small amount of fat administered in this study, but we believe that it reflects the clinical reality, as many patients are unable to consume a full meal when presenting with malaria.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Previous studies in healthy volunteers reported a large impact on the relative bioavailability of piperaquine after a high-fat meal (13, 14). These differences are likely to be explained by the small amount of fat administered in this study, but we believe that it reflects the clinical reality, as many patients are unable to consume a full meal when presenting with malaria.…”
Section: Discussionmentioning
confidence: 94%
“…Sim and colleagues reported a 98% increase in total exposure of piperaquine after a high-fat breakfast (53 g fat) in healthy Caucasian volunteers ( n = 8; crossover design) (13). Nguyen et al reported a more modest 41% increase in total piperaquine exposure after a standardized Vietnamese breakfast (17 g fat) in healthy Vietnamese volunteers ( n = 14; parallel design) (14). However, Hai and colleagues reported no significant impact on piperaquine pharmacokinetics after a similar standardized Vietnamese breakfast (17 g fat) in healthy Vietnamese volunteers ( n = 32; parallel design) (15).…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have investigated the pharmacokinetic properties of piperaquine [6,10,2325,27,29,30,32,35,40,5860]. However, the present study is, to our knowledge, the largest analysis to date, incorporating data from 8,776 pharmacokinetic samples from 728 individuals from different target populations and continents.…”
Section: Discussionmentioning
confidence: 99%
“…For example, drugs such as CQ and MFQ are known to increase the number of gametocytes, which might be problematic assuming antagonism is reproduced in vivo (Price et al., 1996, Buckling et al., 1999). Other drugs such as TFQ, MFQ, LMF, and PPQ have a higher bioavailability when taken with food (Crockett and Kain, 2007, Nguyen et al., 2008). With regard to mixed infections, P. falciparum and P. vivax mixed infections have been reported to show differences in severity, onset of one or the other, and the number of gametocytes etc .…”
Section: Discussionmentioning
confidence: 99%